Inflammatory signature of cerebellar neurodegeneration during neonatal hyperbilirubinemia in Ugt1 -/- mouse model - Vodret, Simone; Bortolussi, Giulia; Jašprová, Jana; Vitek, Libor; Muro, Andrés F (Journal of neuroinflammation, 2017)
BACKGROUND: Severe hyperbilirubinemia is toxic during central nervous system development. Prolonged and uncontrolled high levels of unconjugated bilirubin lead to bilirubin-induced neurological damage and eventually death by kernicterus. Bilirubin neurotoxicity is characterized by a wide array of neurological deficits, including irreversible abnormalities in motor, sensitive and cognitive functions, due to bilirubin accumulation in the brain. Despite the abundant literature documenting the in vitro and in vivo toxic effects of bilirubin, it is unclear which molecular and cellular events actually characterize bilirubin-induced neurodegeneration in vivo. METHODS: We used a mouse model of neonatal hyperbilirubinemia to temporally and spatially define the response of the developing cerebellum to the bilirubin insult. RESULTS: We showed that the exposure of developing cerebellum to sustained bilirubin levels induces the activation of oxidative stress, ER stress and inflammatory markers at the early stages of the disease onset. In particular, we identified TNFα and NFKβ as key mediators of bilirubin-induced inflammatory response. Moreover, we reported that M1 type microglia is increasingly activated during disease progression. Failure to counteract this overwhelming stress condition resulted in the induction of the apoptotic pathway and the generation of the glial scar. Finally, bilirubin induced the autophagy pathway in the stages preceding death of the animals. CONCLUSIONS: This study demonstrates that inflammation is a key contributor to bilirubin damage that cooperates with ER stress in the onset of neurotoxicity. Pharmacological modulation of the inflammatory pathway may be a potential intervention target to ameliorate neonatal lethality in Ugt1 -/- mice.
Keywords: glukuronosyltransferasa; Animals, Newborn; Cerebellum; Inflammation; Ugt1a1; mozeček; degenerace nervu; Astrocytes; zánět; Disease Models, Animal; Autophagy; Hyperbilirubinemia, Neonatal; Mice; Nerve Degeneration; Crigler-Najjar syndrome; novorozená zvířata; Glucuronosyltransferase; myši knockoutované; modely nemocí na zvířatech; zvířata; ER stress; Mice, Knockout; myši; Microglia; novorozenecká hyperbilirubinemie; Oxidative stress; Apoptosis; Animals